2005
DOI: 10.1002/hyp.5583
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in discharge and suspended sediment concentration, including runoff-delaying characteristics, of the Gangotri Glacier in the Garhwal Himalayas

Abstract: Abstract:Diurnal variations in discharge and suspended sediment concentration (SSC), including runoff delaying characteristics, have been studied for the Gangotri Glacier, the largest glacier in the Garhwal Himalayas (glacierized area 286 km 2 ; drainage area 556 km 2 ). Hourly discharge and SSC data were collected near the snout of the glacier (¾4000 m) at an interval of about 15 days for an entire ablation period (May-October 2001). Diurnal variability in SSC was found to be much higher than the discharge. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…Conversely to clockwise behaviour, anticlockwise hysteresis implies that the peak in diurnal discharge leads the peak in diurnal turbidity, indicating that sediments are not as easily mobilized. Diurnal observations of hysteresis in the proglacial river of Rabots glaciär were entirely clockwise, and are therefore comparable with the largely clockwise hysteresis recorded by Singh et al (2005) for Gangotri Glacier in the Himalayas. Data collection in the Gangotri study, however, extended over a full melt season, much longer than our 10 day, non-continuous measurement period.…”
Section: Turbiditysupporting
confidence: 76%
See 1 more Smart Citation
“…Conversely to clockwise behaviour, anticlockwise hysteresis implies that the peak in diurnal discharge leads the peak in diurnal turbidity, indicating that sediments are not as easily mobilized. Diurnal observations of hysteresis in the proglacial river of Rabots glaciär were entirely clockwise, and are therefore comparable with the largely clockwise hysteresis recorded by Singh et al (2005) for Gangotri Glacier in the Himalayas. Data collection in the Gangotri study, however, extended over a full melt season, much longer than our 10 day, non-continuous measurement period.…”
Section: Turbiditysupporting
confidence: 76%
“…4c, such that for equivalent discharge values on the rising and falling limbs of the hydrograph, turbidity is higher on the rising than the falling limb (Hodgkins, 1996). In this context, clockwise hysteresis can be interpreted as easy mobilization of fresh sediment flushed out from channel beds and margins, followed by an exhaustion of sediment supply (Hodgkins, 1996;Singh et al, 2005;Pietrón et al, 2015). Given the short period of time over which turbidity was recorded at Rabots glaciär, it is not possible to investigate multi-day evolution of sediment mobilization over the melt season.…”
Section: Turbiditymentioning
confidence: 99%
“…This indicates that these crevasses may be behaving as a medium of transportation for the large size supraglacial sediments to the subglacial zone where they go through the abrasion process and are flushed out as silt and/or sand size sediments. Our previous hydrological studies have highlighted that englacial and subglacial drainage system becomes progressively better and that the time lag of meltwater becomes smaller with the advancing melt season from May to October (Singh et al, 2005). This indicates clear connections between the supraglacial and subglacial systems, corresponding feedback mechanisms, and evolving glacier dynamics.…”
Section: Subglacial Sediment Evacuationmentioning
confidence: 89%
“…Furthermore, these sediment samples are representative of samples collected twice a day (0830 and 1730 h), during the melt season MayOctober. Timing and frequency of data collection was adopted based on the previous hourly analysis of SSC at Gangotri Glacier during melt season 2001 (Singh et al, 2005). This semimonthly hourly analysis suggested that the morning sample (0830 h) reflects the trough value while the evening sample (1730 h) reflects the peak value of the diurnal SSC cycle.…”
Section: Methodology: Sample Collection and Analysismentioning
confidence: 99%
“…Barnard et al (2004) have made use of cosmogenic radionuclides to date glacial geomorphic features thereby discussing the timing and style of sedimentation and de-sedimentation processes as a response to landscape adjustment with changing environmental conditions in the monsoon influenced dynamic glacial environment of Gangotri. Voluminous work has been carried out by Singh et al (2005Singh et al ( , 2006 on the hydrological characteristics of Gangotri glacier by studying the diurnal variations in suspended sediment load to understand the melt-runoff delays. Haritashya et al (2006Haritashya et al ( , 2010 have carried out particle size distribution and studied the inter-relationships of hydrological variables at Gangotri thus explaining the sediment delivery and evacuation patterns in the light of water resource planning and management.…”
Section: Study Areamentioning
confidence: 99%